2020
DOI: 10.1097/rhu.0000000000001464
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis and Systematic Review of Valvular Heart Disease in Systemic Lupus Erythematosus and Its Association With Antiphospholipid Antibodies

Abstract: Background: Valvular heart disease (VHD) is a known cardiac manifestation of systematic lupus erythematosus (SLE). This systematic review aims to pool data from studies to estimate the frequency of valvular lesions in SLE patients. It also aims to demonstrate the association between VHD in SLE and antiphospholipid antibodies positivity. Methods:We included 27 studies after identifying relevant abstracts from PubMed, Scopus, and Google Scholar from the time of inception of database to 2019. Inclusion criteria c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…A meta-analysis of 1656 patients with SLE concluded that valve disease and vegetations were significantly more prevalent in patients with aPL, ORs of 3.13 (95% CI 2.31 to 4.24) and 3.51 (95% CI 1.93 to 6.38), respectively 15. Another meta-analysis published 10 years later came to a similar conclusion that anti-cardiolipin aPL was associated with valvular disease, although with a lower relative risk of 1.55 (95% CI 1.10 to 2.18) 16…”
Section: Pathophysiology Of Heart Valve Diseasementioning
confidence: 90%
“…A meta-analysis of 1656 patients with SLE concluded that valve disease and vegetations were significantly more prevalent in patients with aPL, ORs of 3.13 (95% CI 2.31 to 4.24) and 3.51 (95% CI 1.93 to 6.38), respectively 15. Another meta-analysis published 10 years later came to a similar conclusion that anti-cardiolipin aPL was associated with valvular disease, although with a lower relative risk of 1.55 (95% CI 1.10 to 2.18) 16…”
Section: Pathophysiology Of Heart Valve Diseasementioning
confidence: 90%
“…Acute MR due to chordal rupture in infancy represents a distinct disease entity, compared to the chordal rupture that is frequently seen in adults due to ischemia or inflammation [ 15 , 20 ]. Valvular regurgitation and rupture in autoimmune diseases in adults are known [ 21 ]. Valvar disease due to dysfunction of the tensor apparatus is a severe complication reported in 1.6% of autoimmune antibody-exposed pregnancies with CHB and 4% of non-CHB cardiac patients [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific manifestations can cause HF in SLE, which has been reported with a prevalence of 1–10% in SLE ( 47 , 50 ). MI and coronary artery disease (CAD) are the leading causes of CVD in these patients ( Figure 2B ), besides being significant risk factors for the development of HF ( 50 ).…”
Section: Cmr Techniquementioning
confidence: 99%
“…The most commonly involved was the mitral valve, with mitral regurgitation being the most common valve disease. Other lesions were mitral stenosis, tricuspid regurgitation ( Figure 2A.e.3 ), and aortic regurgitation ( 47 ). In the same study, the authors found that compared to control subjects, SLE patients had an increased risk of developing valve disease, the highest risk being valvular thickening (RR 6.99, CI 3.64–13.44) and valvular vegetations (RR 7.73, CI 3.09–19.3) ( 47 ).…”
Section: Cmr Techniquementioning
confidence: 99%
See 1 more Smart Citation